2016
DOI: 10.1002/ange.201605132
|View full text |Cite
|
Sign up to set email alerts
|

C−N Bond Formation from a Masked High‐Valent Copper Complex Stabilized by Redox Non‐Innocent Ligands

Abstract: The reactivity of a stable copper(II) complex bearing fully oxidized iminobenzoquinone redox ligands towards nucleophiles is described. In sharp contrast with its genuine low‐valent counterpart bearing reduced ligands, this complex performs high‐yielding C−N bond formations. Mechanistic studies suggest that this behavior could stem from a mechanism akin to reductive elimination occurring at the metal center but facilitated by the ligand: it is proposed that a masked high oxidation state of the metal can be sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…The doublet ground spin state of 5 has been also predicted by DFT calculations (Fig. 34). The UV--vis spectrum of 1 displays around 1200 nm a LLCT band associated with the oxidation of a SQ moiety into BQ, whereas no LLCT can be identified for fully oxidized 5 (Fig.…”
mentioning
confidence: 58%
See 3 more Smart Citations
“…The doublet ground spin state of 5 has been also predicted by DFT calculations (Fig. 34). The UV--vis spectrum of 1 displays around 1200 nm a LLCT band associated with the oxidation of a SQ moiety into BQ, whereas no LLCT can be identified for fully oxidized 5 (Fig.…”
mentioning
confidence: 58%
“…3c and d). 34 Regarding the aziridination reaction (Fig. 3c), the first important observation is the absence of spectral differences between the beginning and the end of the reaction (2h), indicating that the catalytic reaction is extremely fast.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…In a second contribution, the authors reported that the bis-iminobenzoquinone Cu II −CF 3 complex reacted with arylboronic acids to generate the C−N coupling product derived from the oxidation of the ligand scaffold (Figure 80, ii). 306 It was proposed that intramolecular CF 3 − transfer produced a copper(III) complex bearing the oxidized ligand scaffold and an iminosemiquinone radical species (species C in Figure 80). It was also implied that addition of PhB(OH) 2 could generate a copper(II) species with the phenyl bound to the copper in a trans position relative to the CF 3 group (species D in Figure 80).…”
Section: Chemical Reviewsmentioning
confidence: 99%